The Effects of Exposure to Trace Elements on the Skeletal Health of American Mink - Fraschetti, Ariana (My University, 2021)
The release of pollutants by the oil sands industry and pulp and paper mills has been an ongoing environmental concern for decades. Such toxins have been linked to declining reproductive and skeletal health in wildlife species, as they have known endocrine disrupting properties that interfere with hormones responsible for proper reproduction and bone development. As such, declining population sizes because of pollutant exposure has been correlated with altered bone health in mammals. For the purposes of environmental monitoring, the development of a biomarker of pollutant exposure would be a beneficial tool to assess pollution impact on wildlife populations. Therefore, the purpose of this research was to identify this biomarker in the American mink based on measures of their bone health. Mink from the Athabasca Oil Sands Region and an area surrounding a pulp and paper mill in Quebec were collected. From each mink, a hindlimb femur and the baculum (for males) were dissected. Bones were evaluated through a series of tests to quantify key cortical and cancellous bone structural and material properties. These included dimensional analysis, three-point bending and micro-Computed Tomography. Toxicology reports of trace element exposure levels in the minks were also provided by ECCC. Principal component analyses and correlation matrices were used to identify potential relationships between the bone metrics and trace element levels, followed by linear regression modeling. Results found that the baculum and femur structural properties were correlated with selenium, rubidium and iron concentrations, suggesting that these elements had the strongest influences on bone health for the mink studied here. This work provides the basis for future research on identifying a biomarker determinant of bone health to be used in environmental monitoring effects programs. The results here indicate that baculum bone measures are dominated by trace element effects rather than loading effects and are thus a useful bone to investigate for biomonitoring programs. This will provide a simple and reliable method for determining whether there are unsustainable levels of pollution in regions across North America.
Keywords: environmental toxicology; bone; bone health; biomechanics; mink; biomonitoring